2015
DOI: 10.1063/1.4921687
|View full text |Cite
|
Sign up to set email alerts
|

Self-oscillating AB diblock copolymer developed by post modification strategy

Abstract: We prepared AB diblock copolymer composed of hydrophilic poly(ethylene oxide) segment and self-oscillating polymer segment. In the latter segment, ruthenium tris(2,2'-bipyridine) (Ru(bpy)3), a catalyst of the Belousov-Zhabotinsky reaction, is introduced into the polymer architecture based on N-isopropylacrylamide (NIPAAm). The Ru(bpy)3 was introduced into the polymer segment by two methods; (i) direct random copolymerization (DP) of NIPAAm and Ru(bpy)3 vinyl monomer and (ii) post modification (PM) of Ru(bpy)3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…[7,8] To realize autonomous oscillatory behaviors that exist in living systems by using synthetic materials,w eh ave developed "self-oscillating" gels which exhibit autonomous periodic swelling/deswelling changes driven by an oscillatory chemical reaction. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials.…”
mentioning
confidence: 99%
“…[7,8] To realize autonomous oscillatory behaviors that exist in living systems by using synthetic materials,w eh ave developed "self-oscillating" gels which exhibit autonomous periodic swelling/deswelling changes driven by an oscillatory chemical reaction. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials.…”
mentioning
confidence: 99%
“…The efficient redox reaction of Ru(bpy) 3 can be induced by the ideally random arrangement of Ru(bpy) 3 from the viewpoint of the thermodynamic stability of charged structures. [20] From these results, it is expected that autonomous transition between micelles and unimers can be induced in the range of the bistable temperature (25-41 8C) by coupling the BZ reaction, even though the A segment is newly designed as a polycationic BrO 3 À containing hydrophilic polymer. Next, we attempted to induce structural oscillation of the diblock copolymer between micelles and unimers driven by the BZ reaction without the external addition of an oxidizing agent.…”
Section: Communicationsmentioning
confidence: 97%
“…As described in Section 2.1, the post‐modification (PM) method, that is, random copolymerization of NIPAAm and NAPMAm followed by the modification of Ru(bpy) 3 having succinimidyl ester (Ru(bpy) 3 ‐NHS), enables more precise control of self‐oscillating behaviors than the direct polymerization (DP) of NIPAAm and vinyl monomers of Ru(bpy) 3 . We have systematically prepared self‐oscillating diblock copolymers with various compositions of Ru(bpy) 3 via both the DP and PM methods, and investigated the factors that affect the bistable temperature region (Δ T m ) 71. The relationship between the Δ T m and Ru(bpy) 3 composition incorporated into self‐oscillating segments is shown in Figure a.…”
Section: Self‐oscillating Block Copolymersmentioning
confidence: 99%